?ENHANCED DETECTION OF NITROFURANTOIN AS A MUTAGEN BY A MUTATOR R-PLASMID (Biological Sciences - PJSIR, 1998)
Enhanced detection of nitrofurantoin as a chemical mutagen by a novel mutator R-plasmid pEB019 isolated Irorn clinical stool specimen was investigated using Ames reverse mutation assay. Plasmid pEB019 protected E coli WP2 trp, WP2 trp (,lvrA, AB1157,AB1157uvrA tester strains against the bactericidal effects of nitrofurantoin. The mutage- nicity assay results showed that there was no significant NFT-indueed reversion in E coli AB1157prototrophic strain at all concentrations used. There was however, a significant (P < 0.0I) dose-related induced reversion mutation with trains possessing R-plasmid pEB019 and pKM101, but with the former showing a greater activity compared with pKM10I.Reversions in prototrophic and auxotrophic strains, bearing R-plasmid pEB019 were about 10 fold more than the reversion in the isogenic strains without the plasmid. The possible implications of the superior mutability potential of Rvplasmid pEB019 compared with pKMI01 in the monitoring and detection of environmental chemical mutagens using bacterial test system arc highlighted.